Ответы и объяснения

2013-01-27T16:14:23+04:00

1) 3х-15=х+3

2х=18

х=9

 

2) 7-3х=х+11

-4х=4

х=-1

 

3)  2*(х+3)=х+13

2х+6=х+13

х=7

 

4)  4(5-х)=3х-1

20-4х=3х-1

21=7х

х=3

 

2013-01-27T16:22:06+04:00

3х-15=х+3       7-3х=х+11           2(х+3)=х+13      4(5-х)=3х=1

2х=18               2х=4                      2х+6=х+13        20-4х=3х-1

х=9                    х=2                        х=7                      21=7х

                                                                                       х=3